Examining the Impact of Knowledge Mobilization Strategies to Inform Urban Stakeholders on Accessibility: A Mixed-Methods study - Labbé, Delphine (Int J Environ Res Public Health, 2020)
Urban areas offer many opportunities for people with disabilities, but limited accessibility may prevent their full engagement in society. It has been recommended that the experience-based perspective of people with disabilities should be an integral part of the discussion on urban accessibility, complementing other stakeholder expertise to facilitate the design of more inclusive environments. The goals of this mixed-method study were to develop knowledge mobilization (KM) strategies to share experience-based findings on accessibility and evaluate their impact for various urban stakeholders. Using a participatory approach, various KM strategies were developed including videos, a photo exhibit and an interactive game. These strategies were evaluated based on various impact indicators such as reach, usefulness, partnerships and practice changes, using quantitative and qualitative methods. The findings suggested that the KM strategies were effective in raising the awareness of various urban stakeholders and providing information and guidance to urban planning practices related to accessibility.